Large Natural Disasters : Enhancing the Financial Safety Net for Developing Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
The Rapid Credit Facility (RCF) and Rapid Financing Instrument (RFI) are valuable components of the disaster risk financing tool kit for Fund members, especially developing countries. They help to meet urgent balance of payments needs, and are designed to play a catalytic role in mobilizing other external financing. This paper develops proposals for a higher annual access limit under the RCF and RFI, building on a November 2016 staff paper on small states' resilience to natural disasters and climate change (IMF, 2016c). Directors generally supported the proposal in that paper to establish higher annual access limits of 60 percent of quota under the RCF and RFI for countries experiencing severe natural disaster-related damages. The focus of this paper is to specify the threshold of damage from a natural disaster that would allow members experiencing urgent balance of payments needs arising from such disasters to access emergency financing at the higher annual limit. In the November 2016 paper, staff proposed, among other things, the possibility of establishing a higher access limit under the RCF and RFI where the amount of damage reached the threshold of 30 percent of GDP. Most Directors regarded the proposed threshold of disaster damage as overly restrictive, and suggested lowering the threshold to 20 percent of GDP or lower, provided that this did not jeopardize the self-sustainability of the PRGT. For a range of future disaster outcomes, a damage threshold of 20 percent of GDP could increase projected annual average PRGT loan demand in the 1-5 percent range over the next decade, which should not pose significant risks to the robustness of PRGT self-sustainability. Cautious stewardship of PRGT resources argues against a lower disaster damage threshold, pending further experience with disaster trends and associated PRGT loan demand. This paper does not propose changes to the current cumulative access limits for the RCF and RFI. The cumulative access limits play an important role in the Fund's financing architecture, constraining the extent to which countries can access Fund resources without implementing a Fund-supported program with upper credit tranche (UCT) conditionality and associated policies in circumstances where such a program would be more appropriate. The Board will have the opportunity to review the cumulative access limits in the context.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet